Ozonation of a mixture of dialkylphthalates in aqueous solution - Tay, K.S.; Rahman, N.A.; Bin Abas, M.R. (2010)
Ozonation of dimethyl phthalate, diethyl phthalate and dipropyl phthalate was carried out to evaluate the potential of ozonation for phthalate removal from water. Phthalates with longer alkyl chains, which are often more resistant to biodegradation were found to be more degradable than those with shorter alkyl chains. The degradation of phthalates by ozonation follows the pseudo-first-order kinetic model. The rate of phthalates degradation increased exponentially with increasing temperature in the range studied (20 to 50 degrees C) and in proportion with applied ozone dosages. The rate of phthalates degradation was found to increase with increasing pH of the solution from 2.6 to 11.0, and decreased exponentially with increasing initial concentrations of the phthalates. Degradation of phthalates via zonation was found to develop dominantly through direct reaction with hydroxyl radicals. (C) 2010 Society of Chemical Industry